The Use of Web Based Expert System Application for Identification and Intervention of Children with Special Needs in Inclusive School - Dian Atnantomi Wiliyanto (Journal of Education and Learning (EduLearn), 2017)
This research is conducted to determine the effectiveness of web based expert system application for identification and intervention of children with special needs in inclusive school. 40 teachers of inclusive school in Surakarta participated in this research. The result showed that: (1) web based expert system application was suitable with the needs of teachers/officers, had 50% (excellence criteria), (2) web based expert system application was worthwhile for identification of children with special needs, had 50% (excellence criteria), (3) web based expert system application was easy to use, had 52.5% (good criteria), and (4) web based expert system application had result accuracy in making decision, had 52.5% (good criteria). It shows that the use of web based expert system application is effective to be used by teachers in inclusive school in conducting identification and intervention with percentage on average was more than 50%.